Quantitative analysis and discrimination of lard in chicken fat using FTIR spectroscopy and chemometrics for halal authentication - Irnawati, Irnawati; Putri, R. N.; Lestari, L. A.; Rohman, A. (Rynnye Lyan Resources, 2022)
Lard (LD) has a similarity with chicken fat (CF) in terms of physicochemical characteristics especially fatty acid composition and FTIR spectra, therefore, analysis of lard in a binary mixture with CF is challenging. This study aimed to employ FTIR spectra in normal and derivative modes in combination with multivariate calibrations for quantitative analysis of LD and CF in the binary mixture and to discriminate pure LD and LD in the mixture with CF using discriminant analysis (DA). LD and CF were prepared randomly at a certain concentration to be used as calibration and validation sets, respectively. All mixtures were scanned using an FTIR spectrophotometer at 4000-650 cm-1 in absorbance mode. Some wavenumbers, FTIR spectral modes and multivariate calibrations were optimized to provide high accuracy and precision as indicated by the high value of coefficient determination (R2) and low values of errors in calibration and validation. The results revealed that FTIR spectra using normal spectra at combined wavenumbers of 3100-2750 and 1500-660 cm-1 with R2 for the relationship between actual and FTIR predicted values of > 0.99 in calibration and validation with an error in calibration of 0.008 and error validation of 0.032. DA could discriminate LD and LD in the mixture with CF with an accuracy level of 100. FTIR spectroscopy in combination with chemometrics offered a reliable method for quantitative analysis and discrimination of LD in a binary mixture with CF. © 2022, Rynnye Lyan Resources. All rights reserved.